ENGAGEMENT WITH SOCIAL MEDIA CONTENT: A QUALITATIVE EXPLORATION. Issue 1 (3rd April 2018) - Syrdal, Holly A.; Briggs, Elten
Abstract : A lack of a consensus regarding what constitutes engagement in the context of social media has made it difficult for scholars to generate theory in this area and has created challenges for managers attempting to demonstrate positive outcomes stemming from social media marketing. To address this issue, qualitative studies are undertaken with marketing practitioners and consumers to provide clarification and to formulate a formal definition of engagement in this context. The studies reveal it to be a psychological state of mind operating independently from interactive behaviors such as "liking" and sharing content. The findings offer new insight into consumer consumption of social media content and sow the seeds for future exploration.